(untitled) (Advances in Military Technology, 2025)
Range extension of a 120 mm mortar projectile can be attained by a rocket motor within the grenade body. This study deals with the design of experiments-based methodology to identify double-base propellant compositions conceptually feasible for such a motor, from a thermochemical viewpoint. Formulations were defined under low vulnerability and green principles, using Minitab® Statistical Software, following mixture design techniques to account for intrinsic constraints. The thermochemical behavior of these formulations was simulated with a specialized software, taking theoretical characteristic velocity c* as a performance indicator. An empirical model was then fitted, permitting the identification of a set of favorable compositions leading to c* enhancement, regarding a reference double-base propellant, thus unveiling the design possibility of rocket motor downsizing.